Renal Function at Discharge Among Kidney Recipients Experiencing Delayed Graft Function and Its Associations With Long-term Outcomes. Issue 12 (17th November 2022) - Kurian, Sunil M.; Stewart, Darren E.; Toll, Alice; Checchi, Kyle; Case, Jamie; Marsh, Christopher L.
Abstract : Background: Delayed graft function (DGF) after kidney transplantation is associated with higher rates of acute rejection and poor graft survival and outcomes. Current DGF definitions based on posttransplant need for dialysis are not standardized and there are no objective methodologies for quantifying DGF severity. Methods: Using Organ Procurement and Transplantation Network data, we examined DGF, and used recipient serum creatinine at discharge as a correlate of renal function and DGF severity (mild: <2.5 mg/dL; severe: ≥2.5 mg/dL). The associations between donor and recipient factors and DGF severity were quantified using logistic regression. We also examined the associations between DGF severity and long-term recipient outcomes, adjusting for potential confounders. Results: A predictive model using donor and recipient factors had a reasonably good ability to discriminate mild (low creatinine) versus severe (high creatinine) DGF (c-statistic of 0.70). In Cox regression, DGF and creatinine at discharge were both independently associated with long-term outcomes, yet their effects differed depending on the outcome (graft function, death-censored graft function, recipient mortality). Our findings suggest that having DGF, but with relatively good renal function (creatinine <2.5) at discharge, may be less deleterious on graft and recipient survival compared with severe, prolonged DGF, which was associated with a decreased median graft survival of ~2.6 y compared with no DGF with low creatinine at discharge. Conclusions: Our novel DGF severity stratification identified unique factors associated with DGF severity, along with DGF's association with long-term graft and patient survival. The adverse cost and outcome implications of severe DGF warrant additional investigation to improve kidney transplantation practice. Abstract :